The Everyday Literacy Practice of Avatar Creation: Creating a Bridge Between Curriculum Intent and Practice - Connie Morrison (Canadian Society for Studies in Education, 2009)
This paper begins by exploring the chasm that exists between intent and practice within the common English Language Arts Curriculum in Atlantic Canada. As a means to close that gap, it considers how an everyday literacy practice might combine the academic rigor of creating an autobiography with multimodal forms of representation that the curriculum claims to embrace. More specifically, this paper examines how youth might read and represent themselves in the world by combining autobiography, new literacies and technology. Embracing such everyday literacy practices provides another opportunity for educators to fulfill the stated goals for the foundation for the Atlantic Provinces English Language Arts.